Pengembangan Media Cetak dalam Pembelajaran Bahasa Arab - Muhammad Zikran Adam; Muhammad Guntur Firmansyah; Umi Machmudah; Miftahul Huda (Armala, 2023)
Print media has been considered as one of the effective learning media from ancient times even to modern times like now, the use of print media in learning is still quite effective. Therefore this study aims to describe how the development and application of print media in learning Arabic is used as a reference material for educators in developing print-based media in learning Arabic. This research uses a qualitative approach, with the type of research being a literature study. Then, in the process of data collection and analysis techniques, documentation techniques were carried out by collecting and reviewing various journals and articles related to the themes discussed. The results showed that the development of print media such as books, modules, picture cards, posters and bulletins in learning Arabic is still very capable of having a positive impact on students in learning and teaching activities even in an era full of modern technology. Keywords : Print media, Learning Arabic